Density-dependent fitness benefits in quorum-sensing bacterial populations. - Darch, SE; West, SA; Winzer, K; Diggle, S (2012)
It has been argued that bacteria communicate using small diffusible signal molecules to coordinate, among other things, the production of factors that are secreted outside of the cells in a process known as quorum sensing (QS). The underlying assumption made to explain QS is that the secretion of these extracellular factors is more beneficial at higher cell densities. However, this fundamental assumption has never been tested experimentally. Here, we directly test this by independently manipulating population density and the induction and response to the QS signal, using the opportunistic pathogen Pseudomonas aeruginosa as a model organism. We found that the benefit of QS was relatively greater at higher population densities, and that this was because of more efficient use of QS-dependent extracellular "public goods." In contrast, the benefit of producing "private goods," which are retained within the cell, does not vary with cell density. Overall, these results support the idea that QS is used to coordinate the switching on of social behaviors at high densities when such behaviors are more efficient and will provide the greatest benefit.